Immunomodulatory nano-preparations for rheumatoid arthritis - Chenglong Li; Yangyun Han; Xianjin Luo; Can Qian; Yang Li; Huaiyu Su; Guangshen Du (Taylor & Francis Group, 2023)
AbstractRheumatoid arthritis (RA) is a systemic autoimmune disease (AD) caused by the aberrant attack of the immune system on its own joint tissues. Genetic and environmental factors are the main reasons of immune system impairment and high incidence of RA. Although there are medications on the market that lessen disease activity, there is no known cure for RA, and patients are at risk in varying degrees of systemic immunosuppression. By transporting (encapsulating or surface binding) RA-related self-antigens, nucleic acids, immunomodulators, or cytokines, tolerogenic nanoparticles-also known as immunomodulatory nano-preparations-have the potential to gently regulate local immune responses and ultimately induce antigen-specific immune tolerance. We review the recent advances in immunomodulatory nano-preparations for delivering self-antigen or self-antigen plus immunomodulator, simulating apoptotic cell avatars in vivo, acting as artificial antigen-presenting cells, and based on scaffolds and gels, to provide a reference for developing new immunotherapies for RA.